(untitled) (European Journal of Marketing and Economics, 2025)
Until now, in the financial domain, there were only few attempts made to develop maturity models – a useful tool to identify strengths and weaknesses of certain domains of an organization. The aim of this paper is to present a maturity model for management accounting. The method used to develop the model is an interpretive approach, in which an exploratory sequential mixed method research design was applied to broadly explore and understand data on management accounting systems in various settings and in its historical perspective. This study extends my previous research on development of management accounting and financial leadership (Lebedev, 2014, 2015, 2016, 2018, 2019b, 2019a). The framework traces 10 prototype roles of management accounting along their continuum of maturity (from “non-existent” to “strategic leadership”). Each maturity level reflects the extent to which management accounting creates value for its users based on the support provided for “conversations” among stakeholders, the deepness of leadership “embodied” into the management accounting function, and the effectiveness of management accounting principles and management accounting practices (MAPs) employed. This study contributes to the theory of management accounting by offering a framework for understanding of the evolution of financial function and management accounting. In practical terms, the results of the research could be applied to support decisions in transformation of financial function along its maturity continuum (both conducted internally by managers and/or with external support of consultants and advisors), supporting the process of reconciliation of current practices of a company being transformed to a proposed transformational strategy and chosen direction of implementation.